Investigating the above-ground biomass values of sweet potatoes (Ipomoea batatas) - Csatári, Gábor; Koroknai, Judit; Basal, Oqba; Görögh, Panna; Kovács, Szilvia (Acta Agraria Debreceniensis, 2023)
The role of sweet potato tubers in human nutrition is not new. The above-ground biomass of sweet potatoes is not used for nutritional purposes in most countries, but it has a high biological value. Therefore, the aim of the present study is to investigate the production of press fibre from above ground biomass by wet fractionation. Two sweet potato varieties (purple- and white-fleshed sweet potato) and two types of irrigation system were used: bubbling water flow system (BWS) and continuous water flow system (CWS). Glucan, xylan, arabinan were analysed by HPLC and elemental content was measured by ICP-OES. Our results show that the total carbohydrate content in the pressed fibre of the leaf blades (27.64–29.88 %w/w) is lower than in the stem with petiole (51.14–57.36 %w/w). No significant difference in glucan, xylan and arabinan content was observed in the leaf blade. In the stem with petiole, significant differences were observed for xylan and arabinan contents. For elemental content, generally higher values were measured in the leaf blade than in the stem with petiole. This information may be relevant for the selection of the appropriate variety and treatment, even for the production of functional food.